2008
DOI: 10.1152/ajpregu.00190.2008
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac norepinephrine transporter protein expression is inversely correlated to chamber norepinephrine content

Abstract: The cardiac neuronal norepinephrine (NE) transporter (NET) in sympathetic neurons is responsible for uptake of released NE from the neuroeffector junction. The purpose of this study was to assess the chamber distribution of cardiac NET protein measured using [(3)H]nisoxetine binding in rat heart membranes and to correlate NE content to NET amount. In whole mounts of atria, NET was colocalized in nerve fibers with tyrosine hydroxylase (TH) immunoreactivity. NE content expressed as micrograms NE per gram tissue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…But the distribution of NET proteins localized along the fibers in the myocardium may not be consistent with the TH positive fiber density. Recently, Wehrwein et al(2008) reported that the NET protein is colocalized in nerve fibers with TH immunoreactivity in murine atria; however, the NET protein does not correlate with innervation density of murine heart after normalizing to the total protein content of each of the chambers. Rather, NET appears to be equally distributed throughout the myocardium; the total NET protein was highest in the ventricles and lowest in the atria (Wright et al, 2006;Wehrwein et al, 2008).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…But the distribution of NET proteins localized along the fibers in the myocardium may not be consistent with the TH positive fiber density. Recently, Wehrwein et al(2008) reported that the NET protein is colocalized in nerve fibers with TH immunoreactivity in murine atria; however, the NET protein does not correlate with innervation density of murine heart after normalizing to the total protein content of each of the chambers. Rather, NET appears to be equally distributed throughout the myocardium; the total NET protein was highest in the ventricles and lowest in the atria (Wright et al, 2006;Wehrwein et al, 2008).…”
Section: Discussionmentioning
confidence: 98%
“…Recently, Wehrwein et al(2008) reported that the NET protein is colocalized in nerve fibers with TH immunoreactivity in murine atria; however, the NET protein does not correlate with innervation density of murine heart after normalizing to the total protein content of each of the chambers. Rather, NET appears to be equally distributed throughout the myocardium; the total NET protein was highest in the ventricles and lowest in the atria (Wright et al, 2006;Wehrwein et al, 2008). In contrast, postsynaptic effector, β-AR, is uniformly distributed throughout the myocardium, with similar densities in both atrial and ventricular tissues (Hata et al, 2004).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Thus, the reduction of heart NE reuptake is not due to a global reduction in cardiac NET protein expression and there is regional regulation of NET protein. There is a low amount of NET in the atria compared to the ventricles (Wehrwein et al, 2008) and the ventricles have greater uptake capacity compared to the atria so it is unlikely that a reduction in left atrium NET protein in hypertension would be enough to result in a reduction in whole heart uptake. Having ruled out a loss of NET protein in the heart as a cause for reduced reuptake, other factors that could cause a decrease in NE uptake must be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have demonstrated the presence of different components of cholinergic and sympathetic neurotransmission markers as choline and noradrenaline transporters that support the presence of cholinergic and sympathetic nerve cells into the heart [22][23][24][25][26]. Also it has been reported the presence of different neural markers, that suggest the presence of histaminergic, nitrergic, peptidergic, and serotonergic neurotransmission in the same organ [27][28][29].…”
Section: Introductionmentioning
confidence: 95%